The Effect of TikTok Short Video to Improve Students' Speaking Skill in Junior High School - Andi Eka Prasetiani Arinda; Muhammad Zuhri Dj; Siti Nurul Ilmi (Universitas Islam Negeri Palopo, 2026)
This study aimed to investigate the effect of TikTok short videos on improving students' English speaking skills at the junior high school level. Employing a quasi-experimental design with pre-test and post-test control groups, this research involved 60 eighth-grade students at SMP Negeri 6 Watampone in the academic year 2025/2026 as total sampling. The experimental group (Class VIII B, n = 30) received instruction using TikTok short videos (15–60 seconds), while the control group (Class VIII A, n = 30) continued with conventional teaching methods. Speaking performance was assessed through a standardized rubric covering five aspects: pronunciation, fluency, vocabulary, grammar, and comprehension (scored 1–5). Data were analyzed using paired sample t-test and independent sample t-test via SPSS v21.0 at a significance level of p < 0.05. Results showed that the experimental group's mean score increased from 8.10 (pre-test) to 17.60 (post-test), a gain of 9.50 points (t = –15.877, p = 0.000). The control group improved from 7.43 to 15.77, a gain of 8.33 points (t = –11.928, p = 0.000). The independent sample t-test confirmed a statistically significant difference between the two groups' post-test scores (t = 2.264, df = 58, p = 0.027 < 0.05), leading to rejection of the null hypothesis. The largest gains in the experimental group were observed in vocabulary (Δ = 2.10) and grammar (Δ = 2.03). These findings indicate that TikTok short videos are an effective, engaging, and innovative medium for enhancing students' English speaking performance.